Research on reliability assessment and multi-time scale improvement strategy of electricity-gas integrated energy system under cyber attack - Zhao, Zihan; Wang, Yongqi; Jiang, Mengmeng; Liu, Xinrui (Frontiers in Energy Research, 2022)
With the rapid development of the energy industry, the interaction between various energy systems and between energy systems and information networks is becoming more and more in-depth. Security risks also come along with it. For a multi-energy coupled integrated energy system, it is very important to maintain its reliable operation. Therefore, this paper takes the electricity-gas integrated energy system (EGIES) as the research object. Firstly, the cyber-physics system (CPS) model of EGIES is constructed, and the fault propagation mechanism caused by cyber attacks is analyzed. A simulation method of cyber attack scenario based on N-n predicted fault set is proposed. On this basis, a reliability assessment method of EGIES considering cyber attacks is proposed, and the influence of cyber attacks on system reliability is analyzed. Then, on the basis of system reliability assessment, a multi-time scale reliability improvement strategy based on branch power and pipeline flow optimization of EGIES under cyber attack is proposed. Finally, taking IEEE57-NGS20 node EGIES as an example, the effectiveness of the proposed method is verified. The proposed optimization strategy reduces the out-of-limit range of power transmission lines and natural gas pipelines, reduces the probability of cascading failure in the system under information attacks, and improves the resistance and energy supply reliability of the system in the face of cyber attacks.